The determinants of Malaysia export on palm oil / Masayu Othman (Faculty of Business and Management, 2007)
The supply model for crude palm oil was developed to examine the factors affecting palm oil prices. Because of the fluctuation, researcher interested to know about the factors that influence the fluctuation in quantity supply of crude palm oil in Malaysia. The finding indicates that the important determinants of palm oil are the soya bean oil, rapeseed oil and GDP per capita. The objective is to study the trend of crude palm oil, to estimate the determinant on supply of crude palm oil and to analyze the supply elasticity on supply of crude palm oil in Malaysia from 1977 until 2003. To meet the objective, researcher has used three method of the study. For trend analysis, researcher want to estimate the fluctuation happen on independent variable during the period of time. Palm oil export into the other country has fluctuated drastically over the years. Thus, the objective of this study is to investigate the factors that caused the fluctuations. In addition, for supply estimation, researcher used econometric model to analyze the data while determination of supply elasticity was produced single regression line. The study found that there are only three variables that significant with the objective which is price of soya bean oil, price of rapeseed oil and (GDP) per capita. It implies that the overall long-run supply response of crude palm oil in Malaysia between 1977 until 2003 is inelastic. The study also showed that the exchange rate, tallow, kernel oil and crude palm oil were not significant in determining the factor that affect the supply of crude palm oil. The study also revealed that palm oils are held not only for food preparation purposes but also for other reasons such as for biodesel that using in car engine.